2021
DOI: 10.1002/ange.202105383
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Design of Catalytic Lysine‐Targeting Reversible Covalent BCR‐ABL Inhibitors**

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Our examples herein show that targeting the catalytic lysine in protein kinases might hold an advantage in this context. Nonetheless, the mostly similar inhibition profiles between A5 / A11 and PPY‐A against various ABL mutants suggest that the degree of compound selectivity in A5 / A11 , which contained only moderately reactive warheads, [30] largely depended on the initial step of non‐covalent binding. FLT3, a kinase homologous to ABL and previously shown to be cross‐inhibited by PPY‐A, [31] was also potently inhibited by A5 (IC 50 =3.25 nM; Figure S2).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Our examples herein show that targeting the catalytic lysine in protein kinases might hold an advantage in this context. Nonetheless, the mostly similar inhibition profiles between A5 / A11 and PPY‐A against various ABL mutants suggest that the degree of compound selectivity in A5 / A11 , which contained only moderately reactive warheads, [30] largely depended on the initial step of non‐covalent binding. FLT3, a kinase homologous to ABL and previously shown to be cross‐inhibited by PPY‐A, [31] was also potently inhibited by A5 (IC 50 =3.25 nM; Figure S2).…”
Section: Resultsmentioning
confidence: 98%
“…Further evidence of this covalent reversibility was obtained by using 1 H NMR upon dilution with a model complex between 2‐hydroxy‐benzaldehyde and Ac‐Lys‐NHMe (Figure S5) [44] . Further SAR analysis between A5 and A6 indicated that the presence of both OH/CHO and their precise positions were essential for covalent target engagement which was further stabilized by intramolecular H‐bond [30, 44] . By contrast, the Schiff‐base linkage formed between other analogs (such as A8 ) and K271 would be rapidly reversed by hydrolysis.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations